Predictive factor for lymph node metastasis in non-metastatic colorectal adenocarcinomas - Karcı, Ebru; Ürün, Yüksel; Köksoy, Elif Berna; Uçar, Gökhan; Bilgin, Burak; Yekedüz, Emre; Arslan, Çağatay; Alkan, Ali; Dede, İsa; Tuncay, Gülseren; Hocazade, Cemil; Yıldırım Özdemir, Nuriye; et al. (Kare Publishing, 2022)
Objectives: To evaluate the predictive factors of lymph node involvement in non-metastatic colorectal adenocarcinomas (nmCRC). Methods: A total of 453 patients diagnosed with nmCRC were analyzed regarding T stage, lymphovascular invasion status, tumor grade and proposed risk score (RS), determined by the combination of these three factors for lymph node metastasis. Results: The median age was 62 (25-90 years), M/F ratio was 1.4:1 and majority of the patients had tumors localized on the left colon (70.6%). The number of excised lymph nodes was ?12 in 77% of the cases. The postoperative pathological assessments revealed that 57.2% of patie,nts had N0 disease, 29.1% had N1 disease, and 13.7% had N2 disease. The T stages (p=0.007), grade (p<0.001), lymphovascular invasion (p=0.002), RS (p<0.001), and number of excised lymph nodes (p=0.029) were significantly different between N0, N1, and N2 patients. Higher RS was associated with lymph node metastasis (p<0.001). Conclusion: The risk score may predict lymph node metastasis in patients with nmCRC and if validated may be helpful in the decision-making of adjuvant chemotherapy, especially in the elderly and patients with inadequate lymph node dissection.
Keywords: Colorectal Adenocarcinomas; Lymph Node Metastasis; Predictive Factor